THE IMPLEMENTATION OF SUGGESTOPEDIA METHOD TO IMPROVE KINDERGARTEN STUDENTS' ENGLISH VOCABULARIES :A Classroom Action Research at a Kindergarten in Bandung - Afsari Mutiara Maulida Putri, - (2012)
English language especially for kindergarten students. The purpose of this research was to find out the extent to which Suggestopedia can improve kindergarten students' English vocabularies and investigate the students' responses towards the use of Suggestopedia to kindergarten students. A classroom action research was employed at Kindergarten A in Bandung involving 22 students. For the analysis, it used quantitative and qualitative approach to answer the research questions. The data were obtained from several sources, including students' vocabulary assessments, which were developed by Cameron (2000) and Thornbury (2004), classroom observations by the researcher and the class teachers; and interview with the teachers to clarify some bias observation. The findings revealed that there were some improvements of students' English vocabularies and some good responses by producing some language utterance and behavior indicating the students wanted to learn. The data from students' English vocabulary assessments showed that the students' scores significantly improved from the first cycle to the second cycle in recognizing and mentioning English vocabularies. Moreover, data from classroom observations and interviews showed that the students' responses are active, responsive, and enthusiastic toward the use of Suggestopedia method. Based on the findings, it is recommended that teachers who are interested in using Suggestopedia method choose or make a simple story with creative media and acting, especially in the concert stage. Besides that, the activities in practice stage should be more interesting, challenging, and attractive supported by the clear instruction from the teacher.